(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Evidence-based practice (EBP) is essential for high-quality, safe, and cost-effective nursing care. However, its implementation remains limited in many healthcare systems, particularly in low- and middle-income countries. In Kazakhstan, research exploring nurses’ experiences with EBP is scarce, especially from qualitative perspectives. Aim This study aimed to explore nurses’ experiences, perceptions, and challenges in implementing EBP within healthcare settings in Almaty, Kazakhstan. Methods A qualitative descriptive design was employed. Semi-structured interviews were conducted with 74 registered nurses from hospitals and primary healthcare centres. Data were analysed using thematic analysis following Braun and Clarke’s framework. Methodological rigor was ensured through triangulation, audit trails, and collaborative coding. Results Four main themes emerged: (1) understanding and knowledge of EBP, (2) attitudes toward EBP, (3) barriers to EBP implementation, and (4) facilitators and strategies for improvement. Nurses generally recognized the benefits of EBP but reported limited knowledge, heavy workloads, restricted access to evidence resources, and insufficient leadership support. Facilitators included managerial support, protected time for EBP activities, regular training, and standardized clinical guidelines. Conclusions While nurses in Kazakhstan value EBP, multilevel barriers hinder its integration into routine practice. Strengthening organizational support, improving access to scientific evidence, and investing in EBP-focused education are critical to advancing evidence-based nursing. Implications for Practice: Healthcare organizations should prioritize structural, educational, and leadership strategies to support nurses in applying EBP. These include protected time for research and EBP activities, access to scientific databases, continuing professional development, and the implementation of standardized clinical guidelines. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 751-757